Educational research in architecture: ICT tool for historical buildings evaluation - Virtudes, Ana L. (2020)
Historical buildings have been threatened by the vulnerability to degradation. This problem is not an exception in Portugal, where the few remaining examples of vernacular architectural wooden stilt-houses of river banks, have been neglected, with the disappearance or abandonment of almost all buildings. This research presents the results of an educational research in architecture, creating a software for evaluation of status of historical buildings conservation. It will present as a case study, the portuguese wooden stilt-house village of Lezirão, where this ICT (information and communication technology) platform was tested. This is one of the remaining five vernacular architectural villages of river banks that still exist in the country, nearby Tagus river. This research was developed in a PhD thesis in Architecture at the University of Beira Interior in Covilhã. This ICT platform is a pioneer approach in educational research in architecture, related on wooden stilt-houses evaluation in Portugal and it can be used in other similar buildings all over the world.